Kinetics of nonisothermal reduction and carburization of WO3─NiO nano‐composite powders by CO─CO2. Issue 7 (28th March 2019) - Mohammadzadeh, Hurieh; Rezaie, HamidReza; Barati, Mansoor; Yu, Dawei; Samim, Hamid Reza
Abstract: The kinetics of simultaneous reduction and carburization of WO3 ─NiO nanocomposite powders by CO/CO2 was studied using a nonisothermal thermogravimetric analysis. The experiments were carried out at heating rates between 5 and 15°C/min, showing that the thermochemical processes can be divided into four steps, each dominated by a reaction, as following: NiO → Ni, WO3 → WO2, WO2 → W, and W → WC. The apparent activation energy for each step was obtained based on the Flynn‐Wall‐Ozawa isoconversional method for the individual steps, and the kinetic model was assessed by fitting master plots of various kinetic models for these steps at different heating rates. The Avrami‐Erofeev kinetic model was found to fit to the third and fourth steps and main part of the first, and the geometric contracting model fitted the best for the second step. Changing the heating rate did not affect the master plots of the third step. However, for the first step, increasing the heating rate made the Avrami‐Erofeev model the best‐fitting correlation and also for the second step the matching model changed at the highest heating rate (15°C/min) from a two‐dimensional contracting model (cylindrical particles) to a three‐dimensional contracting model (spherical particles).